Synthesis, Characterization and Antimicrobial Evaluation of Schiff Bases of 4-Amino-5-(4-Tert-butylphenyl)-4H-1,2,4-Triazole-3-Thiol - Kapri, Kamal Prasad; Shakya, Bhushan (Journal of Nepal Chemical Society, 2018)
Available with full text.